Partial trisomy 9p and partial monosomy 7p of an infant inherited from maternal balanced translocation: a case report - Rui Li; Chaojie Wang; Zhenhua Zhang; Dongxiao Li; Lifeng Li; Ding Zhao; Zhaojie Xu (BMC, 2023)
Abstract Background Subchromosomal deletions and duplications are the leading cause of congenital malformations and mental retardation in children. With the recent clinical application of genomic microarrays in the evaluation of patients with developmental delays and congenital malformations, it has led to the discovery of several new microdeletion and microduplication syndromes. However, there are no published reports involving patients with both microduplications in the 9p21.1-p24.3 region and microdeletions in the 7p22.1-p22.3 region. Case presentation We report an infant with an autosomal abnormality confirmed by conventional karyotype combined with copy number variations sequencing (CNV-seq), showing the patient with an unbalanced translocation. The karyotype of the patient was 46, XX, der (7)t (7;9) (p22; p21) and CNV-seq results showed an approximately 32.34-Mb duplication in 9p21.1-p24.3 (200000-32540000) and an approximately 3.3-Mb deletion in 7p22.2-p22.3 (40000-3340000). Conclusions The patient carried an unbalanced translocation 46, XX, der (7)t (7;9) (p22; p21) derived from her mother. The clinical presentation is closely related to the size and position of the missing and duplicated chromosomes. To our knowledge, the simultaneous occurrence of de novo partial trisomy 9p(9p21.1-p24.3) and partial monosomy 7p (7p22.2-p22.3) has not previously been reported up until now. The present study additionally demonstrated that CNV-seq combined with karyotype is able to reliably detect unbalanced submicroscopic chromosomal aberrations.